Doenças de veiculação hídrica na sub-bacia do Rio Ganhamoroba, Maruim - Sergipe - Barros, Itamar Prado (2014)
The research aims to analyze waterborne diseases in the villages of São Vicente, Estação and Arapiraca in the city of Maruim , Sergipe. In this context we started from the particular to the general, analyzing waterborne diseases in order to diagnose their causes and effects. This study was developed through visits in the area; application of questionnaires to 94 householders in the months from November 2012 to September 2013. It was analyzed water from Ganhamoroba River, natural sources, wells and four residences (tap water), for performing microbiological and physical-chemical analysis. Samples of surface water, groundwater and tap water were collected in five steps. Documents provided by epidemiological health service were analyzed; the reports of the team five of the Family Health Medical Program and the registration form of the families supplied by the health agent. From the conceptual model called Driving Force - Pressure - State - Exposure - Effect - Action (DPSEEA) WHO, it was constructed a scheme to analyze the relationship between environment - sanitation - health. Approximately 77% of the homes have water from artesian wells without treatment. The streets do not have paving and sewage; garbage collection is poor and inadequate. The results of the microbiological analyzes of water from the six sampling sites show that 100% of these are contaminated by total coliforms and Escherichia coli. Of 390 residents, 52 were reported in the period from 2009 to March 2013 with schistosomiasis. It was concluded that the search for targeted social policies for housing is extremely important to this community that goes through various problems. As a solution we present the construction of houses in an area near the old church of São Vicente through a partnership of Maruim City Hall, Pinheiro Factory, Petrobras and Inorcal Factory; paving the streets of the villages; increasing and treating the water from the artesian well that was drilled by the city hall, as well as monthly cleaning of the water tank; educating the population in other to not use water from the river and natural sources without treatment.